IOT-Based Bengawan Solo River Water Discharge Increase Marker System (Internet of Things) - Anggita, Febri Arif; Maulindar, Joni; Susanto, Rudi (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2024)
When the rainy season comes, the water in the Bengawan Solo river will experience an increase in water discharge and will result in the area being flooded in the watershed area so that the community will suffer material and life losses. So that a device to detect the increase in water discharge is injured remotely, to give a sign that the water has increased so that the community can save valuable goods. So that the community does not suffer many losses and can immediately evacuate goods and souls to a safe place. This research aims to create a device to detect the increase in water discharge in the Bengawan Solo river remotely. In making the tool, the author uses the prototype development method, the author searches for data with various sources and types of data. The author collected data from interviews with local residents and related agencies. From this study, the author produced a system to detect the increase in water discharge and type of rain by using a water level sensor, rain sensor and ESP 32 microcontroller which can be monitored through a telegram application remotely using an internet connection. The tool made by the author can detect the river water level from level 3, level 2 and level 1 and also detect the type of rain that occurs around the river.